KAJIAN PENJAJAKAN DESA BINAAN: RANTAU BINUANG SAKTI - Ediwarman Ediwarman; T Iskandar Johan; Saipul Bahri; Ujang Paman Ismail; Mukhtar Ahmad (UIR Press, 2015)
In order to make a decision on the possibility to determine Rantau Binuang Sakti to be an established village of the Islamic University of Riau, a reconnaissance study have conducted as a field study in the mid-January 2015. As an origin of traditional village, which has been famous since in the mid 16th century, but the village are closed and isolated due to bad infrastructure conditions and seemingly rural development program has not yet been in touch to the village, by regency as well as by other upper government institution. The natural resources as a part of the Rokan river wetland area, it well support of the important of fishery to Rokan Hulu Regency, so that recently it will be one of the fishing recreation tourism come from various cities such as Pekanbaru and Duri. Base on the main scientific priority and the persistent of Islamic University of Riau’s expertise on the rural and community development, so that Rantau Binuang Sakti is feasible then as a rural reconstruction of the Islamic University of Riau by means to strengthen the fishery and its resources, develop creative economy embedded with spiritual and eco-tourism as well as possible to be a potential production center for horticultural fruit for the region (inhabitant) consumption.